Morphological Verb Valency Driven Errors of Secondary School Students - Öztürk, Burcu; Çiçek, Seher (Australian International Academic Centre, 2021)
The aim of the current study is to determine the distribution of verb valency-driven errors of secondary school students. To this end, this study is framed as a survey research. The sample of the study consists of 200 secondary school students in three schools with different socio- economic levels. The content and teaching of morphological verb valency and the problems encountered were elaborated in the light of Turkish teachers’ views. The data of the study were compiled through document analysis. Frequency analysis was employed to determine the occurrence of morphological verb valency driven errors. Besides, content analysis was used to analyse teachers’ views. The research findings revealed that secondary school students made verb valency driven errors at 393 times while using 145 different verbs. The mean value of verb valency driven errors per student was 1.96. Furthermore, the verbs with the most common verb valency driven errors were respectively as follows: çık- (to leave), al- (to take), bul- (to find), söyle- (to tell), yaşa- (to live), git- (to go), gör- (to see), ver- (to give), çöz- (to solve) and gel- (to come). Teachers, however, stated that students had difficulty in analysing and writing morphemes in morphological verb valency, and they, in particular, made verb valency driven errors in long sentences in writing and speaking skills. Moreover, activities towards knowledge and comprehension in terms of words and sentences are inadequate in respect to such cognitive processes such as synthesis and evaluation of texts. Therefore, it is recommended that teaching of morphological valency should be integrated with language skills in order to minimize morphological verb valency driven errors that have an impact upon literacy skills of students in their mother tongue.
Keywords: 4. Education